Hydrography‐Driven Coarsening of Grid Digital Elevation Models. Issue 5 (21st May 2018) - Moretti, Giovanni; Orlandini, Stefano
Abstract: A new grid coarsening strategy, denoted as hydrography‐driven coarsening, is developed in the present study. The hydrography‐driven coarsening is designed to retain the essential hydrographic features of valleys and channels observed in high‐resolution digital elevation models: (1) depressions are filled in the considered high‐resolution digital elevation model, (2) the obtained topographic data are used to extract a reference grid network composed of all surface flow paths, (3) the Horton order is assigned to each link of the reference grid network, and (4) within each coarse grid cell, the elevation of the point lying along the highest‐order path of the reference grid network and displaying the minimum distance to the cell center is assigned to this coarse grid cell center. The capabilities of the hydrography‐driven coarsening to provide consistent surface flow paths with respect to those observed in high‐resolution digital elevation models are evaluated over a synthetic valley and two real drainage basins located in the Italian Alps and in the Italian Apennines. The hydrography‐driven coarsening is found to yield significantly more accurate valley and channel profiles than existing coarsening strategies. In absolute terms, the obtained valleys and channels compare favorably with those observed. In addition, the proposed coarsening strategy is found to reduce drastically the impact of depression‐filling in the obtained coarse digital elevation models. The hydrography‐driven coarsening strategy is therefore advocated for all those cases in which the relief of the extracted drainage network is an important hydrographic feature. Plain Language Summary: High‐resolution digital elevation models (grid cell size of 1 m or less) generated from light detection and ranging (lidar) surveys are making detailed topographic descriptions of drainage basins increasingly available. On the other hand, grid coarsening is often necessary to meet computational constrains in detailed, large‐scale, and/or long‐term hydrologic simulations. While nearest neighbor coarsening remains the standard strategy, more complex coarsening strategies with special focus on drainage basin hydrology have recently been proposed. However, existing coarsening strategies may not capture important hydrographic features observed in high‐resolution topographic data. Existing coarsening strategies may cause significant alterations of land surface topography, especially when depression‐filling procedures are applied to coarsened digital elevation models. It is, therefore, relevant to seek grid coarsening strategies that can better retain the hydrographic features observed in high‐resolution digital elevation models, and that can have beneficial implications on the description of surface flow propagation, hyporheic fluxes, and hydrologic interactions between hill slope and channel networks. A hydrography‐driven coarsening strategy is developed and tested in the present study. This strategy is found to significantly improve the capabilities of existing coarsening strategies to yield accurate descriptions of valleys and channels in coarse digital elevation models. Key Points: A new strategy for coarsening high‐resolution grid digital elevation models is developed to retain observed valley and channel profiles This hydrography‐driven coarsening strategy yields valleys and channels that compare favorably with those observed The hydrography‐driven coarsening drastically reduces the impact of depression‐filling in the obtained coarse digital elevation models